Fault Current Limiter Using YBCO Coated Conductor-The Limiting Factor and Its Recovery Time - Baldan, Carlos Alberto [UNESP]; Lamas, Jerika Suely; Shigue, Carlos Yujiro; Ruppert Filho, Ernesto (Institute of Electrical and Electronics Engineers (IEEE), 2009)
A fault current limiter (FCL) based on an arrangement of parallel connected high temperature superconducting tapes constituting a limiter element was designed and tested in 220 V line for a fault current peak between 1 kA to 2 kA. The limiter employed second generation (2G) HTS tapes of YBCO coated conductor reinforced with stainless steel. Four tapes were electrically connected in parallel with 0.4 m effective length per element wherein 16 elements connected in series constitutes a single-phase unit. The FCL performance was evaluated through over-current and current fault tests. Its recovery characteristics were used to design the shunt protection. The designed limiting ratio is 4 for 16 elements and the experimental result for one element showed a 20% limiting ratio. For the fault current test one element can withstand five cycles of fault without degradation. It was observed recovery times below 0.5 s under nominal load using a shunt resistance of 173 m Omega.
Keywords: Current limiting ratio; superconducting fault current limiter; YBCO coated conductor; YBCO recovery characteristics